Strategi Bimbingan Konseling dalam Perspektif Islam untuk Meningkatkan Prestasi Belajar serta Akhlak Peserta Didik - Kharisma Noor Latifatul Mahmudah; Wantini Wantini; Ruri Afria Nursa (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2020)
This research aims to watch the extent of guidance and counseling teacher services in improving student learning achievement shape Islamic morals on students. This research approach is a qualitative research with a descriptive approach. The data source of this research was through the assistance and role of the Guidance and Counseling teacher to 88 students who were sampled. Data collection instruments were carried out by interview and questionnaire. The collected data is then collected, analyzed and interpreted into a whole new concept and also fres. The result of the research is the role of the guidance teacher has included a good classification. But there are still several factors that cause students to experience learning difficulties, for example, factors from within the individual consisting of physiological and psychological factors. Physiological factors are physical conditions and the five senses. While psychological factors, namely talent, interest, intelligence, achievement motivation and cognitive abilities. While the Guidance and Counseling teacher strategy in improving student learning achievement, for example, is correlating between the Guidance and Counseling teacher with parents or homeroom teachers who know the learners' personalities in depth to better know what problems have occurred.